MINDFUL CONSUMPTION BEHAVIOR ON SECOND-HAND FASHION PRODUCTS: INTERVARIABLE INFLUENCE ANALYSIS OF STIMULUS-ORGANISM-RESPONSE (S-O-R) MODEL - Gabriella, Diyang Risma; Hardjanto, Ramses Wardhana; Mawaridi, Muhammad Fadhil; Harits, Muhammad Naufal; Purnami, Luh Dyah (ASEAN Marketing Journal, 2021)
Manuscript type: Empirical Research Research Aims: This study was conducted to analyze and develop the intervariable influence within stages in S-O-R Model in second-hand fashion products context Design/methodology/approach: To fulfill the research objective, an online self-administered survey was conducted to respondents who had second-hand thrifting purchase experience. 130 eligible responses were gathered and further analyzed using Structural Equation Modeling (two-way approach) Research Findings: It is observed that eWOM and Consumer Engagement have positive significant effects on Mindful Consumption Behavior (MCB), while no significant influence is found in relationship Attitude toward MCB. No mediating effect is observed in relationship eWOM toward MCB through mediating variable Attitude and Consumer Engagement. Theoretical Contribution/Originality: This research contributes to provide insight on factors that influence mindful consumption behavior in Indonesia Practitioner/Policy Implication: Based on the result of this research, related stakeholder can utilize eWOM and encourage consumers to form mindful consumption behavior (i.e: through social connection that would increase consumers' enthusiasm and attention towards MCB) Research limitation/Implications: The study is limited as it only analyzed some variables to predict consumer behavior in fashion thrifting. Based on the research, eWOM and Consumer Engagement are proven to influence MCB, and there is no effect observed of Attitude on MCB. Therefore, this research contributes to consumer behavior that proves eWOM and Engagement are strong predictors to predict consumer behavior in the purchase of second-hand fashion.